A graft copolymer and its preparation method and application

By grafting PET and/or sugar compounds into polyolefin block copolymers, a new type of graft copolymer is prepared, which solves the problem of poor modification effect of polyolefin materials in the prior art, and achieves the effect of improving the compatibility of ternary blended plastics.

CN116535656BActive Publication Date: 2025-04-04XIHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310691954.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2025-04-04
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

In the prior art, when modifying polyolefin materials, the olefin block copolymer can only serve as a toughening agent but not as a compatibilizer, resulting in poor modification effect and lack of effective compatibilizer for ternary and above polymer mixed systems.

Method used

A novel graft copolymer is prepared by grafting polyethylene terephthalate (PET) and/or sugar compounds into polyolefin block copolymers for improving compatibility between single-use ternary blended plastics.

Benefits of technology

The resulting graft copolymer can significantly improve the compatibility between non-polar polyolefins and polar polymers, improve the comprehensive performance of composite materials, and reduce the difficulty of classification during plastic recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116535656B_ABST
    Figure CN116535656B_ABST
Patent Text Reader

Abstract

The present invention relates to a graft copolymer and a preparation method thereof and an application thereof in a compatibilizer, and belongs to the field of polymers. The present invention provides a preparation method of a graft copolymer, wherein the preparation method comprises: using a polyolefin block copolymer, PET and a saccharide compound as raw materials, grafting PET and the saccharide compound into the polyolefin block copolymer under the action of an initiator to obtain the graft copolymer; wherein the ratio of the polyolefin block copolymer, PET and the saccharide compound is: 100 parts by weight of the polyolefin block copolymer, 0 to 20 parts by weight of PET, 0 to 20 parts by weight of the saccharide compound, and 0.2 to 2 parts by weight of the initiator; and the amount of PET and the saccharide compound cannot be 0 at the same time. The obtained graft copolymer can significantly improve the compatibility between non-polar polyolefins and polar polymers, improve the comprehensive performance of composite materials, reduce the difficulty of classification during plastic recycling, and promote economic circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graft copolymer and a preparation method thereof and application of the graft copolymer in a compatibilizer, belonging to the field of polymers. Background Art

[0002] Polyolefin block copolymer is a block copolymer made of polypropylene (PP) and polyethylene (PE). It is a kind of thermoplastic elastomer. It has a certain compatibility with polyolefin plastics and is generally used as a toughening agent for polyolefin modified materials. However, olefin block copolymer is a non-polar material. When polyolefin is blended with polar materials for modification, olefin block copolymer can only act as a toughening agent but not a compatibilizer, which makes the modification effect poor.

[0003] The most common method of compatibilization is to add amphiphilic compatibilizers, mainly including block / graft copolymers. Existing compatibilizers include using PP-PE block copolymers to compatibilize PP / PE blends, PP-g-MAH or PP-g-GEM to compatibilize PP / PE blends and PP / PET blends, PE-g-MAH to compatibilize PP / PE blends and PE / PET blends, or SEBS-g-MAH to compatibilize PE / PET blends and PP / PET blends.

[0004] In addition, the current field of polymer compatibilization is limited to binary polymer alloy compatibilization. For ternary and higher polymer mixed systems, there are no reports of effective compatibilizers due to their complexity. Summary of the invention

[0005] In view of the above-mentioned defects, the present invention provides a novel graft copolymer that can be used as a compatibilizer, which is a novel copolymer that can be used as a compatibilizer and is prepared by grafting polyethylene terephthalate (PET) and / or a sugar compound into a polyolefin block copolymer; the obtained copolymer can improve the compatibility between disposable ternary blended plastics (such as ternary plastic blends of PE, PP and PET), and the polarity is enhanced by grafting the polyolefin block copolymer to PET, so that its side chain and the PET in the blend are co-crystallized or bulk entangled; the sugar compound is grafted to the polyolefin block copolymer, so that the sugar compound side chain of the compatibilizer and the PET in the blend undergo ester exchange reaction or hydrogen bond connection, and the biodegradability of the compatibilizer or the compatibilized blend is enhanced.

[0006] The technical solution of the present invention:

[0007] The first technical problem to be solved by the present invention is to provide a method for preparing a graft copolymer, the preparation method comprising: using a polyolefin block copolymer, PET and a sugar compound as raw materials, grafting PET and / or the sugar compound into the polyolefin block copolymer under the action of an initiator to prepare the graft copolymer; wherein the ratio of the polyolefin block copolymer, PET and the sugar compound is: 100 parts by weight of the polyolefin block copolymer, 0 to 20 parts by weight of PET, 0 to 20 parts by weight of the sugar compound, and 0.2 to 2 parts by weight of the initiator; and the amounts of PET and the sugar compound cannot be 0 at the same time.

[0008] Furthermore, the ratio of the polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of polyolefin block copolymer, 1-20 parts by weight of PET, 0-20 parts by weight of sugar compound, and 0.2-2 parts by weight of initiator.

[0009] Furthermore, the ratio of the polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of polyolefin block copolymer, 0-20 parts by weight of PET, 1-20 parts by weight of sugar compound, and 0.2-2 parts by weight of initiator.

[0010] Furthermore, the ratio of the polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of polyolefin block copolymer, 1 to 20 parts by weight of PET, 1 to 20 parts by weight of sugar compound, and 0.2 to 2 parts by weight of initiator.

[0011] Furthermore, the polyolefin block copolymer is a PP-PE multi-block copolymer, preferably a PP-PE diblock copolymer.

[0012] Furthermore, the carbohydrate compound is a polysaccharide, an oligosaccharide or a monosaccharide.

[0013] Furthermore, the polysaccharide is selected from: starch, chitosan, cellulose, alginic acid or alginate, etc.

[0014] Furthermore, the oligosaccharide is selected from: disaccharide, trisaccharide or tetrasaccharide, etc.

[0015] Furthermore, the monosaccharide is selected from: glucose, fructose, galactose or ribose.

[0016] Furthermore, the initiator is dicumyl peroxide, di-tert-butyl peroxide or ammonium cerium nitrate.

[0017] Furthermore, the preparation method is: firstly dissolve or swell the polyolefin block copolymer, PET and sugar compound in a solvent respectively, then react at 100-140°C for 2-6 hours under the action of an initiator, cool and precipitate, filter, and then dry at 60-80°C for 8-12 hours to obtain the polymer.

[0018] Furthermore, the solvent is tetrachloroethane.

[0019] Furthermore, the preparation method of the polymer comprises the following steps:

[0020] (1) dehumidifying and drying the polyolefin block copolymer, PET and the saccharide compound, and then fully dissolving or swelling them in a solvent at 100 to 140° C.;

[0021] (2) adding part of the initiator to the dissolved polyolefin block copolymer, reacting at 100-140° C. for 10-30 min, adding the dissolved PET, and reacting at the same temperature for 2-4 h; then adding the remaining initiator and the dissolved sugar compound, and continuing the reaction for 2-4 h;

[0022] (3) pouring the product obtained in step (2) into a low boiling point solvent to cool and precipitate, and filtering; then drying at 60 to 80° C. for 8 to 12 hours to obtain the polymer.

[0023] Furthermore, in step (3), the low boiling point solvent is: dichloromethane, petroleum ether or anhydrous ethanol.

[0024] The second technical problem to be solved by the present invention is to provide a graft copolymer prepared by the above method.

[0025] Further, the structure of the polymer is:

[0026] The third technical problem to be solved by the present invention is to point out that the above graft copolymer is used as a solubilizer for polyolefin blending materials; that is, the graft copolymer obtained by the present invention can be used to improve the compatibility between non-polar polyolefins and polar polymers.

[0027] Furthermore, it is used as a compatibilizer for PP, PE and PET blends.

[0028] Beneficial effects of the present invention:

[0029] The present invention grafts polyethylene terephthalate (PET) and / or sugar compounds into polyolefin block copolymers under the action of an initiator to prepare a novel graft copolymer that can be used as a compatibilizer; the obtained graft copolymer can significantly improve the compatibility between non-polar polyolefins and polar polymers. It can be seen that the present invention uses low-cost raw materials to prepare a degradable compatibilizer, which can enhance the compatibility of disposable blended plastics, improve the comprehensive performance of composite materials, reduce the difficulty of classification during plastic recycling, and promote economic circulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1The schematic diagram of the synthesis reaction of the graft copolymer used as a compatibilizer in the present invention.

[0031] Figure 2 The infrared spectra of the products obtained in Examples 1 (SBP), 6 (BP) and 7 (BS).

[0032] Figure 3 The figure is the hydrogen NMR spectrum of the polymer obtained in the example of the present invention. DETAILED DESCRIPTION

[0033] The invention relates to a novel copolymer which can be used as a compatibilizer and is prepared by grafting polyethylene terephthalate (PET) and / or a sugar compound into a polyolefin block copolymer. The obtained copolymer can improve the compatibility between disposable ternary blended plastics (such as ternary blends of PE, PP and PET). By grafting the polyolefin block copolymer onto PET, the polarity is enhanced, so that its side chain and the PET in the blend undergo co-crystallization or bulk entanglement. By grafting the sugar compound onto the polyolefin block copolymer, the sugar compound side chain of the compatibilizer undergoes an ester exchange reaction or hydrogen bond connection with the PET in the blend, and the biodegradability of the compatibilizer or the compatibilized blend is enhanced. That is, the obtained copolymer can improve the toughness and stiffness of the composite material.

[0034] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0035] Example 1

[0036] A method for preparing a compatibilizer for ternary blended plastics:

[0037] Weigh 10 grams of dried raw materials PP-PE diblock copolymer (brand: D5545.00), 0.6 grams of PET (brand: WB-8816) and 0.4 grams of sugar compound corn starch, and dissolve or swell the raw materials in 70 ml, 20 ml and 15 ml of tetrachloroethane respectively. The dissolution temperatures are 120°C, 140°C and 90°C respectively, and the dissolution time is 1-2 hours.

[0038] Add 0.06 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer and react at 130°C for 10 min; then add the dissolved PET, react for 2 h, add 0.04 g of initiator ammonium cerium nitrate, and then add the dissolved sugar compound and react for 2 h. Pour the product into dichloromethane, cool it, precipitate it and filter it, then dry it at 60°C for 8-12 h to obtain the target product (SBP, infrared spectrum as shown in the figure Figure 2 ).

[0039] Example 2

[0040] A method for preparing a biodegradable compatibilizer for ternary blended plastics:

[0041] On the basis of Example 1, the system was adjusted to 10 g of PP-PE diblock copolymer, 0.6 g of PET and 0.8 g of sugar compound corn starch, and the raw materials were dissolved in 70 ml, 20 ml and 25 ml of tetrachloroethane respectively; the dissolution temperatures were 120°C, 140°C and 90°C, and the dissolution time was 1-2 h.

[0042] Add 0.06 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer, react at 130°C for 10 min, then add the dissolved PET, react for 2 h, add 0.08 g of initiator ammonium cerium nitrate, then add the dissolved sugar compound, and react for 2 h. Pour the product into dichloromethane, cool and precipitate, filter, and then dry at 60°C for 8-12 h to obtain the target product (SBP, see Figure 2 ).

[0043] Example 3

[0044] A method for preparing a biodegradable compatibilizer for ternary blended plastics:

[0045] On the basis of Example 2, the system was adjusted to 10 g of PP-PE diblock copolymer, 0.6 g of PET and 1.2 g of sugar compound corn starch, and the raw materials were dissolved or swelled in 70 ml, 20 ml and 30 ml of tetrachloroethane respectively; the dissolution temperatures were 120°C, 140°C and 90°C, and the dissolution time was 1-2 h.

[0046] Add 0.06 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer, react at 130°C for 10 min, then add the dissolved PET, react for 2 h, add 0.12 g of initiator ammonium cerium nitrate, then add the dissolved sugar compound, and react for 2 h. Pour the product into dichloromethane, cool and precipitate, filter, and then dry at 60°C for 8-12 h to obtain the target product (SBP, see Figure 2 ).

[0047] Example 4

[0048] A method for preparing a biodegradable compatibilizer for ternary blended plastics:

[0049] On the basis of Example 1, the system was adjusted to 10 g of PP-PE diblock copolymer, 0.9 g of PET and 0.4 g of sugar compound corn starch, and the raw materials were dissolved in 70 ml, 25 ml and 15 ml of tetrachloroethane respectively; the dissolution temperatures were 120°C, 140°C and 90°C, and the dissolution time was 1-2 h.

[0050] Add 0.09 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer, react at 130°C for 10 min, then add the dissolved PET, react for 2 h, add 0.04 g of initiator ammonium cerium nitrate, then add the dissolved sugar compound, and react for 2 h. Pour the product into dichloromethane, cool and precipitate, filter, and then dry at 60°C for 8-12 h to obtain the target product (SBP, see Figure 2 ).

[0051] Example 5

[0052] A method for preparing a biodegradable compatibilizer for ternary blended plastics:

[0053] Based on Example 1, the system was adjusted to 10 g of PP-PE diblock copolymer, 1.2 g of PET and 0.4 g of corn starch, and the raw materials were dissolved in 70 ml, 30 ml and 15 ml of tetrachloroethane respectively. The dissolution temperatures were 120°C, 140°C and 90°C, and the dissolution time was 1-2 h.

[0054] Add 0.12 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer, react at 130°C for 10 min, then add the dissolved PET, react for 2 h, add 0.04 g of initiator ammonium cerium nitrate, then add the dissolved corn starch, and react for 2 h. Pour the product into dichloromethane, cool and precipitate, filter, and then dry at 60°C for 8-12 h to obtain the target product (SBP, see Figure 2 ).

[0055] Example 6

[0056] A method for preparing a compatibilizer for ternary blended plastics:

[0057] On the basis of Example 1, the system was adjusted to 10 g of PP-PE diblock copolymer and 0.6 g of PET, and the raw materials were dissolved in 70 ml and 20 ml of tetrachloroethane respectively. The dissolution temperature was 120° C. and 140° C., and the dissolution time was 1-2 h.

[0058] 0.06 g of initiator ammonium cerium nitrate was added to the dissolved PP-PE diblock copolymer, and the reaction was carried out at 130°C for 10 min, followed by the addition of dissolved PET for 2 h, and then the product was poured into dichloromethane, cooled and precipitated, and filtered, and then dried at 60°C for 8-12 h to obtain the target product (BP, see Figure 2 ).

[0059] Example 7

[0060] A method for preparing a compatibilizer for ternary blended plastics:

[0061] Weigh 10 g of the dried raw materials PP-PE diblock copolymer and 0.4 g of corn starch, and dissolve or swell the raw materials in 70 ml and 15 ml of tetrachloroethane respectively. The dissolution temperatures are 120° C. and 90° C., and the dissolution time is 1-2 h.

[0062] Add 0.04 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer, react at 130°C for 10 min, then add swollen corn starch and react for 2 h. Pour the product into dichloromethane, cool and precipitate, filter, and then dry at 60°C for 8-12 h to obtain the target product (BS, see Figure 2 ).

[0063] Example 8

[0064] A method for preparing a compatibilizer for ternary blended plastics:

[0065] Weigh 10 g of the dried raw materials PP-PE diblock copolymer and 0.4 g of glucose, and dissolve or swell the raw materials in 70 ml and 15 ml of tetrachloroethane respectively. The dissolution temperatures are 120° C. and 90° C., and the dissolution time is 1-2 h.

[0066] Add 0.04 g of initiator ammonium cerium nitrate to the dissolved PP-PE diblock copolymer, react at 130°C for 10 min, then add swollen glucose and react for 2 h. Pour the product into dichloromethane, cool and precipitate, filter, and then dry at 60°C for 8-12 h to obtain the target product.

[0067] Test Example 1

[0068] Test method for compatibilization of ternary plastic blends.

[0069] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, take 4 parts of the compatibilizer prepared in Example 1, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5min. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 641% and its elastic modulus is 512MPa. The raw material ratios and performance results of each test example and comparative example are shown in Table 1.

[0070] Test Example 2

[0071] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 2, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 498%, and its elastic modulus is 474MPa.

[0072] Test Example 3

[0073] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 3, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 395%, and its elastic modulus is 476MPa.

[0074] Test Example 4

[0075] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 4, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 667% and its elastic modulus is 487MPa.

[0076] Test Example 5

[0077] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 5, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 646%, and its elastic modulus is 448MPa.

[0078] Test Example 6

[0079] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 6, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 150%, and its elastic modulus is 457MPa.

[0080] Test Example 7

[0081] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 7, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 610%, and its elastic modulus is 467MPa.

[0082] Test Example 8

[0083] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and 4 parts of the compatibilizer prepared in Example 8, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 830%, and its elastic modulus is 430MPa.

[0084] Comparative Example 1

[0085] Weigh 41 parts of dried PP, 30 parts of PE, and 29 parts of PET, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then, it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then, a tensile test is performed at a rate of 1mm / min, and the elongation at break is measured to be 9%, and the elastic modulus is 232MPa.

[0086] Comparative Example 2

[0087] Weigh 41 parts of dried PP, 30 parts of PE, 29 parts of PET, and take 4 parts of PP-PE diblock copolymer as a compatibilizer, mix them evenly by physical stirring, and then add them into a twin-screw extruder for melt blending. The blend is blended at 255-260°C at a speed of 10-20rpm for 5 minutes. Then it is injection molded into dumbbell-shaped specimens at 250-255°C, and the mold temperature is 25-40°C. Then a tensile test is performed at a rate of 1mm / min, and its elongation at break is measured to be 61% and the elastic modulus is 401MPa.

[0088] Table 1 Raw material ratio and performance comparison of each test example and comparative example

[0089]

[0090] It can be seen from the comparative examples and specific embodiments that the compatibilizer of the present invention can effectively improve the compatibility between polyolefin and polar polyester, and provides an effective solution for the preparation of biodegradable plastics and large-scale recycling of waste plastics.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a graft copolymer, characterized in that: The preparation method comprises the following steps: using polyolefin block copolymer, PET and sugar compound as raw materials, grafting PET and sugar compound into polyolefin block copolymer under the action of initiator to obtain the graft copolymer; wherein the ratio of polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of polyolefin block copolymer, 0-20 parts by weight of PET, 0-20 parts by weight of sugar compound and 0.2-2 parts by weight of initiator; and the amounts of PET and sugar compound cannot be 0 at the same time.

2. The method for preparing a graft copolymer according to claim 1, characterized in that: The ratio of the polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of the polyolefin block copolymer, 1 to 20 parts by weight of PET, 0 to 20 parts by weight of the sugar compound, and 0.2 to 2 parts by weight of the initiator; or: The ratio of the polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of the polyolefin block copolymer, 0-20 parts by weight of PET, 1-20 parts by weight of the sugar compound, and 0.2-2 parts by weight of the initiator; or: The ratio of the polyolefin block copolymer, PET and sugar compound is: 100 parts by weight of polyolefin block copolymer, 1-20 parts by weight of PET, 1-20 parts by weight of sugar compound and 0.2-2 parts by weight of initiator.

3. The method for preparing a graft copolymer according to claim 1, characterized in that: The polyolefin block copolymer is a PP-PE multi-block copolymer.

4. The method for preparing a graft copolymer according to claim 1 or 2, characterized in that: The carbohydrate compound is polysaccharide, oligosaccharide or monosaccharide.

5. The method for preparing a graft copolymer according to claim 4, characterized in that: The polysaccharide is selected from: starch, chitosan, cellulose, alginic acid or alginate; The oligosaccharide is selected from: disaccharide, trisaccharide or tetrasaccharide; The monosaccharide is selected from the group consisting of glucose, fructose, galactose or ribose.

6. The method for preparing a graft copolymer according to claim 1 or 2, characterized in that: The initiator is dicumyl peroxide, di-tert-butyl peroxide or cerium ammonium nitrate.

7. The method for preparing a graft copolymer according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: firstly dissolving or swelling the polyolefin block copolymer, PET and the sugar compound in a solvent respectively, then reacting at 100 to 140° C. for 2 to 6 hours under the action of an initiator, cooling to precipitate, filtering, and then drying at 60 to 80° C. for 8 to 12 hours to obtain the polymer.

8. A graft copolymer, characterized in that The graft copolymer is prepared by the method according to any one of claims 1 to 7.

9. Use of the graft copolymer prepared by the method according to any one of claims 1 to 7, characterized in that: Compatibilizer for polyolefin blends.

10. The use according to claim 9, characterized in that The polyolefin blend material is a blend material of PP, PE and PET.

Citation Information

Patent Citations

  • PET alloy material, special compatibilizer thereof and preparation method thereof

    CN101671420A

  • Method for grafting polymer chain employing biomass polysaccharide

    CN104419008A